2009
DOI: 10.1111/j.1365-2648.2009.04997.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of performance feedback on tracheal suctioning knowledge and skills: randomized controlled trial

Abstract: Retention of knowledge and tracheal suctioning practice is improved when training is followed up by tailored feedback on performance. Further research would shed light on how long such improvements are sustained, and whether the improvements seen in a simulated setting can be generalized to clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 32 publications
3
27
1
8
Order By: Relevance
“…Slaugytojas turi turėti pakankamai kompetencijos nuspręsti apie sekreto išsiurbimo iš tracheostomos vamzdelio būtinumą. Užsienio šalyse atlikti tyrimai rodo, kad slaugytojai, atlikdami tracheostomos priežiūrą, ne visada remiasi įrodymais pagrįsta praktika [17][18][19][20][21]. Day T., Iles N., Griffiths P. (2009) teigimu, nepakanka įvertin-ti slaugytojų teorines žinias, nes jos gali prastai atspindėti praktiką [19].…”
Section: įVadasunclassified
See 1 more Smart Citation
“…Slaugytojas turi turėti pakankamai kompetencijos nuspręsti apie sekreto išsiurbimo iš tracheostomos vamzdelio būtinumą. Užsienio šalyse atlikti tyrimai rodo, kad slaugytojai, atlikdami tracheostomos priežiūrą, ne visada remiasi įrodymais pagrįsta praktika [17][18][19][20][21]. Day T., Iles N., Griffiths P. (2009) teigimu, nepakanka įvertin-ti slaugytojų teorines žinias, nes jos gali prastai atspindėti praktiką [19].…”
Section: įVadasunclassified
“…Užsienio šalyse atlikti tyrimai rodo, kad slaugytojai, atlikdami tracheostomos priežiūrą, ne visada remiasi įrodymais pagrįsta praktika [17][18][19][20][21]. Day T., Iles N., Griffiths P. (2009) teigimu, nepakanka įvertin-ti slaugytojų teorines žinias, nes jos gali prastai atspindėti praktiką [19]. Todėl šio tyrimo metu buvo siekiama sužii -noti, kokios yra slaugytojų žinios apie tracheostomos priežiūrą ir nustatyti, ar turimos žinios taikomos klinikinėje praktikoje.…”
Section: įVadasunclassified
“…Moreover, they found that there was a considerable difference reflected in nurses' performance between ideal standard ES where nurses followed the recommended guidelines and actual routine technique when nurses didn't. (17)(18)(19)(20) Additionally, Day et al (17) and Sole et al (19) stated that practice of ES was not always based on current research recommendations, which may lead to inconsistent practice among nurses, affecting patients' experience and increasing health risks associated with ES so it is necessary to examine the actual routine method of ES practiced by nurses in ICU and its effect on patient's condition in comparison with the standard ES that follows evidenced based recommendation. Based on this, the aim of this study was to evaluate effect of application of endotracheal suction guidelines on cardiorespiratory parameters of mechanically ventilated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Organisational changes within trusts to place tracheostomy and laryngectomy patients on to designated wards will concentrate skills, experience and equipment and provide relevant and consistent medical support, with improvements in patient care described [27,48,49,[142][143][144][145][146].…”
Section: Discussionmentioning
confidence: 99%